Маркетинговые исследования: сущность, методы, технологии - Полторак, В. (Социология: теория, методы, маркетинг, 2000)
The article is a brief review of the "Marketing Research" textbook on the course being boundary between applied sociology, economy and marketing. On the one hand, its goalis to show to sociologists-beginners what an essence and specific character of applied marketing research are, on the other hand, to present specific methods and technologiesused for the market research by economists and students of Economy Departments. There have been discussed the basic marketing research directions (including marketing environment and consumers), special methods used in marketing research (including quality methods, trade and consumer panels, omnibus, hall-tests, focus-groups), specific character of marketing research technologies.